Evaluation of IT-Investments - Rózsa, Tünde (Acta Agraria Debreceniensis, 2005)
An informatical innovation is essentially a private business in the life of a venture but the ability of evolution and adaptability of ventures is remarkable for the national economy too. This is why it is important to observe the economical effects of IT investments. The introduction of an information system – as in the cases of other investments – requires pre- and post-calculations for payback of fixed assest, thrift and profitability. The operation of an information system means not only one-off acquisition of instruments and intangible assets, but requires continuous development, version control and improvement of hardware in the sake of conservation. There is a high rate of depreciation of IT investments in Hungary, because such goods change too quickly, together with the economic environment. If the conservation of IT instrument value wanted one has to make new expansions continually. IT specialists have determined some indices, one of which is Total cost of Ownership, which is an important indicator for investment analysis. In practice, there are some other models and methods we can adopt in our analysis. In this paper, I collected several relevant and usable methods for pre analysis of IT projects. Management can adopt these models in his investment process to make sound decisions.